2016
DOI: 10.1371/journal.pone.0148973
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Diagnostic Strategy for Parotid Gland Tumors Using Diffusion-Weighted MRI and Technetium-99m Pertechnetate Scintigraphy: A Prospective Study

Abstract: ObjectiveFine needle aspiration cytology (FNAC) for diagnosis of a parotid gland tumor is widely used but its sensitivity is low and non-diagnostic rate is relatively high. In contrast, core needle biopsy (CNB) has a higher sensitivity and lower rate of sampling errors but has a higher risk of injury to adjacent organs such as facial nerve than FNAC. Screening of patients with parotid gland tumors to identify cases of pleomorphic adenoma (PA) and Warthin tumor (WT) may allow CNB to be confined to patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Our study showed that the mean ADC is significantly higher in PMAs than in WTs, no matter whether on FSE‐PROP‐DWI or SS‐EP‐DWI. Our results are consistent with the majority of earlier studies on SS‐EP‐DWI but different to Fruehwald‐Pallamar et al's study, in which there was no difference between mean ADC in PMAs and WTs . Our results also showed that the FSE‐PROP‐DWI and the SS‐EP‐DWI both allow distinguishing PMAs from WTs significantly.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study showed that the mean ADC is significantly higher in PMAs than in WTs, no matter whether on FSE‐PROP‐DWI or SS‐EP‐DWI. Our results are consistent with the majority of earlier studies on SS‐EP‐DWI but different to Fruehwald‐Pallamar et al's study, in which there was no difference between mean ADC in PMAs and WTs . Our results also showed that the FSE‐PROP‐DWI and the SS‐EP‐DWI both allow distinguishing PMAs from WTs significantly.…”
Section: Discussionsupporting
confidence: 89%
“…Metallic dental implants‐related magnetic susceptibility artifacts, motion artifacts and involuntary bulk motion‐related signal loss have been found to affect the imaging quality of SS‐EP‐DWI in parotid glands. Geometric distortion has also been demonstrated in SS‐EP‐DWI, not only in healthy parotid glands but also in parotid gland tumors …”
Section: Introductionmentioning
confidence: 89%
“…A low ADC indicates decreased diffusion of water molecules in tissue, suggesting more cellular tissue. Generally, malignant tumors tend to have lower ADC than benign tumors [ 18 ]. WT may be differentiated from malignant lesions based on “hot” uptake with 99m Tc pertechnetate scintography, which is due to the epithelial component's ability to concentrate 99m Tc pertechnetate but not secrete it [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, malignant tumors tend to have lower ADC than benign tumors [ 18 ]. WT may be differentiated from malignant lesions based on “hot” uptake with 99m Tc pertechnetate scintography, which is due to the epithelial component's ability to concentrate 99m Tc pertechnetate but not secrete it [ 18 , 19 ]. WT also exhibits intense uptake on FDG-PET/CT [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic MRI was performed using a 1.5 T scanner (Avanto, Siemens AG, Healthcare Sector, Erlangen, Germany). The MRI protocol used has been described elsewhere . Briefly, non–contrast‐enhanced T1‐weighted images, T2‐weighted images, and diffusion‐weighted images with b values of 0 and 1,000 sec/mm 2 were acquired in the axial plane.…”
Section: Methodsmentioning
confidence: 99%